Association Between Autonomic Impairment and Structural Deficit in Parkinson Disease. Issue 11 (March 2016) - Chen, Meng-Hsiang; Lu, Cheng-Hsien; Chen, Pei-Chin; Tsai, Nai-Wen; Huang, Chih-Cheng; Chen, Hsiu-Ling; Yang, I-Hsiao; Yu, Chiun-Chieh; Lin, Wei-Che
Abstract : Abstract: Patients with Parkinson disease (PD) have impaired autonomic function and altered brain structure. This study aimed to evaluate the relationship of gray matter volume (GMV) determined by voxel-based morphometry (VBM) to autonomic impairment in patients with PD. Whole-brain VBM analysis was performed on 3-dimensional T1-weighted images in 23 patients with PD and 15 sex- and age-matched healthy volunteers. The relationship of cardiovascular autonomic function (determined by survey) to baroreflex sensitivity (BRS) (determined from changes in heart rate and blood pressure during the early phase II of the Valsalva maneuver) was tested using least-squares regression analysis. The differences in GMV, autonomic parameters, and clinical data were correlated after adjusting for age and sex. Compared with controls, patients with PD had low BRS, suggesting worse cardiovascular autonomic function, and smaller GMV in several brain locations, including the right amygdala, left hippocampal formation, bilateral insular cortex, bilateral caudate nucleus, bilateral cerebellum, right fusiform, and left middle frontal gyri. The decreased GMVs of the selected brain regions were also associated with increased presence of epithelial progenitor cells (EPCs) in the circulation. In patients with PD, decrease in cardiovascular autonomic function and increase in circulating EPC level are associated with smaller GMV in several areas of the brain. Because of its possible role in the modulation of the circulatory EPC pool and baroreflex control, the left hippocampal formation may be a bio-target for disease-modifying therapy and treatment monitoring in PD.